The Use of Animated Video Media in Mathematics Learning: A Literature Review - Nilawati Nilawati; Septiana Dwi Cahyani; Aulia Aulia; Gunawan Gunawan; Nina Nisrina (Indonesian Journal of STEM Education, 2025)
This study aims to analyze the effectiveness of animated video media in mathematics learning through a literature review approach. This research is motivated by the lack of comprehensive studies that synthesize findings across educational levels and research methods regarding the use of animated videos in mathematics learning. The method used is a literature review by analyzing 15 scientific articles published in national and international journals during 2015-2024, selected based on inclusion and exclusion criteria. The data were analyzed using a descriptive-synthesis approach to identify research trends, implementation forms, and their impacts on learning outcomes. The results indicate that animated video media consistently show positive effects on students’ conceptual understanding, learning motivation, and engagement. Most studies employed Research and Development (R&D) and experimental methods, with dominant implementation at the elementary and junior high school levels. However, the effectiveness of animated videos is influenced by factors such as media design, interactivity, and learning context. Therefore, animated video media can be an effective alternative learning tool when designed appropriately.